Processes and mechanisms of vegetation ecosystem responding to climate and ecological restoration in China - Chen, Tiantian; Wang, Qiang; Wang, Yuxi; Peng, Li (Frontiers in Plant Science, 2022)
Vegetation is an essential component of the earth’s surface system and is a clear indicator of global climate change. Probing the long-term characteristics of vegetation changes and their relation to climate and human activities is important for regional sustainable development and ecological construction. Here, the normalized difference vegetation index (NDVI) was selected as a proxy, and ensemble empirical mode decomposition and the Breaks for Additive Seasonal and Trend algorithm were applied to reconstruct the NDVI data (i.e. noise, annual, interannual) and to diagnose spatiotemporal evolution and abrupt changes in long-term vegetation trends in China during 1982–2018. Residual analysis was used to separate the influence of climate and human activities on NDVI variations, and spatial partitioning of the driving factors was obtained. The results suggest that there was noticeable vegetation recovery (slope = 0.0015/yr, p <0.001), and the boundary of high and low NDVIs was close to the Hu Line. Based on the time-varying analysis, high vegetation browning was masked by overall vegetation greening. Vegetation growth in China experienced an abrupt change in the 1990s and 2000s, accounting for 50% and 33.6% of the whole of China respectively. Of the area before the breakpoint, 45.4% showed a trend of vegetation decrease, which was concentrated mainly in east China, while 43% of the area after the breakpoint also showed vegetation degradation, mainly in northwest China. Climate was an important driving force for vegetation change in China. It played a positive role in south China, but had a negative effect in northwest China. The impact intensity of human activities on vegetation changes was lower than that of climate, and it changed from an initial negative influence to a positive one. In terms of human activities, an inverted-U-shaped relation was detected between CO2 emissions and vegetation growth; that is, the fertilization effect of CO2 had a certain threshold. Once that threshold was exceeded, it would hinder vegetation growth. Population density had a slight constraint on vegetation growth, and the implementation of ecological restoration projects (e.g., the Grain for Green Program) can promote vegetation growth to a certain extent